COMPILING VOCABULARY LISTS FOR CORPUS-BASED ARABIC FOR TOURISM TEACHING - Hendra, Faisal; Rufaidah, Mujahidah Fharieza (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Arabic for Tourism is a course that can be facilitated with innovative teaching materials along with the availability of learning resources on the internet rich in vocabulary and terms typical to the field of Arabic tourism. Therefore, the use of Arabic tourism websites is an effective way to compile vocabulary lists. The articles published in this kind of websites can be collected to be used as a corpus, then processed using a corpus processing software, AntConc. This study used a combination of qualitative and quantitative approaches with descriptive and comparative methods using a corpus linguistic approach. Teachers can take advantage of the features in this application to identify vocabularies commonly used in the world of tourism. These features are word frequency, concordance, collocation, and N-Gram. The results can be used as a reference in compiling an Arabic for Tourism vocabulary list.